2016
DOI: 10.1177/1526602816669135
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the Femoropopliteal Segment

Abstract: The deformation characteristics of the femoropopliteal segment change in the presence of a stent, with the change to the deformation behavior dependent on stent type, stent length, location, flexibility, and intrinsic centerline curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…No stent appears to accommodate all deformation modes without either exacerbating or restricting baseline deformations. Restriction of foreshortening within the stented segment observed in this study agrees with previous findings in patient 4,19 , cadaver 20 , and computational models 21 , and the amount of restriction for different devices correlates with device stiffness in compression determined with bench-top tests 8 . In these tests the Viabahn stent-graft restricted foreshortening the least, likely due to its helically wrapped wire around specially designed PTFE fabric, while most other devices contained multiple, rigid longitudinal connectors that restricted foreshortening.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No stent appears to accommodate all deformation modes without either exacerbating or restricting baseline deformations. Restriction of foreshortening within the stented segment observed in this study agrees with previous findings in patient 4,19 , cadaver 20 , and computational models 21 , and the amount of restriction for different devices correlates with device stiffness in compression determined with bench-top tests 8 . In these tests the Viabahn stent-graft restricted foreshortening the least, likely due to its helically wrapped wire around specially designed PTFE fabric, while most other devices contained multiple, rigid longitudinal connectors that restricted foreshortening.…”
Section: Discussionsupporting
confidence: 91%
“…Braided-wire and wrapped-wire stents on the other hand demonstrated more gentle curvatures in bench-top experiments (Figure 8), and produced less acute bending in situ. Effects of bending stiffness on curvature have been previously reported in cadaver models 20 and PAD patients 4 where kinks similar to those described in Figure 4C were observed at the distal end of some stents.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, Ghriallais et al . 89 reported that axial compression and curvature of the FPA change in the presence of the stent, with the amount of change dependent on stent characteristics. No studies were found to investigate torsion of the stented FPA.…”
Section: Femoropopliteal Artery Obstructive Diseasementioning
confidence: 99%
“…As the SFA is a long, relatively straight vessel, it is exposed to low wall shear under resting conditions [ 9 ]—a circumstance that predisposes it to atherosclerotic disease while also serving as a factor that confounds the healing process after endovascular injury. Implantation into the SFA of a stent with a straight cylindrical configuration will act to further straighten the vessel, so that while the stent may restore vessel patency, it can alter effective arterial flexibility and reduce the capability of the vessel to shorten naturally (as in an unstented state), opening the way for kinking and buckling of the vessel at the ends of the stented segment as well as for possible stent fracture [ 5 ]. The introduction of a straight stent may jeopardize the antirestenotic swirling blood flow commonly imparted by the natural helical arterial geometry.…”
Section: The Biomimics 3d Helical Centerline Stentmentioning
confidence: 99%